AFRICAN SWINE FEVER EPIDEMIC IN 2007–2017 PART 1. COMMON TRENDS FOR ASF IN THE RUSSIAN FEDERATION AND IN EURASIA - A. S. Oganesyan; М. A. Shibayev; Н. Ye. Baskakova; F. I. Korennoy; A. К. Karaulov (Ветеринария сегодня)
Results of retrospective analysis of African swine fever epidemic situation in the Russian Federation including analysis of the epidemic chronology indicating significant events of the disease spread across the country territory are presented. Common ASF epidemic trend and rate in 2007–2017 in Eurasia territory based on number of infected countries (1.273 ± 1.272 countries/year) and in Russian Federation Subjects (4.5 ± 2.3 Subjects/year) are shown. The paper also addresses some peculiarities of the epidemic process depending on the season of a year. Possible social and biological factors contributing to the epidemic spread are examined. Necessity of further search for probable biological vector and examination of social factors that could contribute to the disease maintenance in wild life and in domestic pigs in the Russian Federation and Eastern European countries are discussed.